A halogen-free flame-retardant power cable and a preparation method thereof

By adding the prepared flame-retardant and smoke-suppressing microspheres to the power cable, the problem of insufficient flame-retardant and smoke-suppressing performance of the power cable is solved, the halogen-free flame retardant effect is achieved, and the risk of secondary fire disasters is reduced.

CN118956044BActive Publication Date: 2025-01-24HEBEI JIN GREATWALL CABLE CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411455079.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-01-24
Estimated Expiration
2044-10-18

AI Technical Summary

Technical Problem

The flame retardant and smoke suppressing performance of existing power cables is insufficient, and commonly used halogen-containing flame retardants will produce toxic and harmful gases and smoke when burned at high heat, threatening life and safety.

Method used

Halogen-free flame-retardant power cables are prepared by adding flame-retardant and smoke-suppressing microspheres. Flame-retardant and smoke-suppressing microspheres are made from cyanuric chloride, p-aminobenzenesulfonic acid, sodium carbonate and other compounds through a series of reactions. They have a nitrogen-phosphorus expansion flame-retardant system and good smoke absorption capabilities.

Benefits of technology

It realizes the good flame retardant and smoke suppression performance of the power cable, while avoiding the use of halogen -containing compounds, reducing the occurrence of secondary disasters of fire.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the field of power cables, and in particular to a halogen-free flame-retardant power cable and a preparation method thereof. The halogen-free flame-retardant power cable comprises a core, a shielding layer and an outer sheath layer from the inside to the outside, wherein the outer sheath layer is made of a blended masterbatch, wherein the blended masterbatch comprises the following raw materials in parts by weight: 60-70 parts of low-density polyethylene, 10-15 parts of high-density polyethylene, 1-3 parts of a peroxide cross-linking agent, 0.8-1 parts of a lubricant and 6-8 parts of flame-retardant and smoke-suppressing microspheres; by adding the flame-retardant and smoke-suppressing microspheres, the problem of insufficient flame-retardant and smoke-suppressing performance of existing power cables is solved, and at the same time, the addition of halogen-containing compounds is avoided to reduce the occurrence of secondary fire disasters.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of power cables, and in particular to a halogen-free flame-retardant power cable and a preparation method thereof. Background Art

[0002] Power cables are an important part of the power system and are responsible for the transmission and distribution of electrical energy. As the raw material used in cables second only to metals, polymers are mainly used in the preparation of insulation layers, sheaths and filling materials for wires and cables. The application of polymer materials in cables mainly plays a role in assisting the processing and molding of cables, protecting metal conductors and ensuring the electrical insulation performance of cables.

[0003] Polyethylene is widely used in cable sheaths because of its excellent mechanical, electrical insulation, processing properties, and excellent dielectric properties in a wide frequency range. However, polyethylene materials are extremely flammable, and flame retardants are often added to make them flame-retardant. However, common halogen-containing flame retardants will produce a large amount of toxic and harmful gases and smoke during high-temperature combustion, threatening people's lives and safety. Summary of the invention

[0004] The purpose of the present invention is to provide a halogen-free flame-retardant power cable and a preparation method thereof, which solves the problem of insufficient flame-retardant and smoke-suppressing performance of existing power cables by adding flame-retardant and smoke-suppressing microspheres, while avoiding the addition of halogen-containing compounds and reducing the occurrence of secondary fire disasters.

[0005] The object of the present invention can be achieved by the following technical solution: A halogen-free flame-retardant power cable, which comprises a core, a shielding layer and an outer sheath layer from the inside to the outside, wherein the outer sheath layer is made of a blended masterbatch;

[0006] A method for preparing a halogen-free flame-retardant power cable comprises the following steps: Step S1: weighing the following raw materials in parts by weight: 60-70 parts of low-density polyethylene, 10-15 parts of high-density polyethylene, 1-3 parts of peroxide cross-linking agent, 0.8-1 parts of lubricant and 6-8 parts of flame-retardant and smoke-suppressing microspheres, mixing the low-density polyethylene, high-density polyethylene, peroxide cross-linking agent, lubricant and flame-retardant and smoke-suppressing microspheres and adding them to a twin-screw extruder, extruding and granulating to obtain a blended masterbatch;

[0007] Step S2: passing the copper wire into a wire drawing machine, drawing, annealing, and twisting the wire to obtain a wire core, wrapping a mica tape around the outside of the copper-clad aluminum wire core to form a shielding layer, and then extruding the outside of the shielding layer with a blended masterbatch as a raw material to form an outer sheath layer, steam cross-linking, cooling in a water tank, and air-drying in a drying machine to obtain a halogen-free flame-retardant power cable;

[0008] The flame retardant and smoke suppression microspheres are prepared by the following steps:

[0009] Step A1: cyanuric chloride, p-aminobenzenesulfonic acid, sodium carbonate and deionized water are mixed, and sodium bicarbonate solution is added under stirring at a rate of 100-120 rpm and a temperature of 5°C, and the pH is adjusted to 3, and the reaction is carried out for 1-1.5 hours to obtain intermediate 1; intermediate 1, acetone and deionized water are mixed, and ammonia water and sodium hydroxide solution are added under stirring at a rate of 100-120 rpm and a temperature of 60°C, and the reaction is carried out for 3-4 hours to obtain intermediate 2;

[0010] The mass concentration of the sodium bicarbonate solution is 7.5%, the dosage ratio of cyanuric chloride, p-aminobenzenesulfonic acid, sodium carbonate and deionized water is 0.2 mol: 0.2-0.22 mol: 10-11 g: 150-160 mL, the molar concentration of ammonia water is 10 mol / L, the molar concentration of the sodium hydroxide solution is 1 mol / L, and the dosage ratio of the intermediate 1, acetone, deionized water, ammonia water and sodium hydroxide solution is 0.2 mol: 150-160 mL: 60-70 mL: 40-45 mL: 30-40 mL;

[0011] During the reaction, at a temperature of 5°C, the chlorine in cyanuric chloride reacts with the amino group in p-aminobenzenesulfonic acid to obtain intermediate 1, and then at a temperature of 60°C, the chlorine in intermediate 1 reacts with ammonia water to form an amino group to obtain intermediate 2;

[0012] Step A2: formaldehyde and deionized water are mixed, and melamine and intermediate 2 are added under stirring at a rate of 120-150 rpm and a temperature of 80°C, and the mixture is reacted for 20-30 minutes, and then a formic acid solution is added, and the mixture is reacted for 1 hour, centrifuged, and dried to obtain modified microspheres; the modified microspheres, urea, polyvinyl pyrrolidone and deionized water are mixed, and ferric chloride is added under stirring at a rate of 120-150 rpm and a temperature of 90°C, and the mixture is reacted for 6-8 hours, centrifuged, and dried to obtain composite microspheres;

[0013] The molar concentration of the formic acid solution is 1 mol / L, the dosage ratio of formaldehyde, deionized water, melamine, intermediate 2 and formic acid solution is 20-22 mL: 300 mL: 0.02-0.025 mol: 0.01-0.012 mol: 1-1.5 mL, and the dosage ratio of modified microspheres, urea, polyvinyl pyrrolidone, deionized water and ferric chloride is 2.5-3 g: 0.8-1.2 g: 15-16 g: 80-100 mL: 1.2-1.4 g;

[0014] During the reaction, formaldehyde first reacts with melamine and the amino group in intermediate 2 to form hydroxymethyl groups, and then undergoes a dehydration condensation reaction under acidic conditions to obtain modified microspheres. Since the surface of the modified microspheres contains a large number of sodium sulfonate groups, ferric chloride is used as the iron source to grow rod-shaped oxyhydroxide iron on the surface of the modified microspheres by a hydrothermal method to obtain composite microspheres.

[0015] Step A3: Stir β-cyclodextrin, triphenylphosphine, p-hydroxyanisole and acetone at a stirring rate of 200-300 rpm and a temperature of 50°C, add pyrophosphoric acid, and react for 24 hours to obtain phosphated cyclodextrin; mix composite microspheres, phosphated cyclodextrin, potassium carbonate and tetrahydrofuran, and stir for 24 hours at a stirring rate of 80-100 rpm and a temperature of 85°C to obtain flame retardant and smoke suppression microspheres;

[0016] The dosage ratio of β-cyclodextrin, pyrophosphoric acid, triphenylphosphine and p-hydroxyanisole is 11.2-11.9 g: 0.08-0.1 mol: 0.5-0.6 g: 0.3-0.4 g; the dosage ratio of composite microspheres, phosphated cyclodextrin, potassium carbonate and tetrahydrofuran is 0.1-0.12 g: 0.2-0.3 g: 0.15-0.18 g: 50-60 mL;

[0017] During the reaction, under the action of triphenylphosphine and p-hydroxyanisole, the hydroxymethyl group in β-cyclodextrin reacts with pyrophosphoric acid to introduce a phosphate group to obtain phosphated cyclodextrin, and then the flame retardant and smoke suppression microspheres are obtained through the host-guest inclusion reaction between the ferric hydroxide in the composite microspheres and the cyclodextrin in the phosphated cyclodextrin.

[0018] The present invention discloses a halogen-free flame-retardant power cable and a preparation method thereof, and the beneficial effects are as follows:

[0019] 1. By adding flame retardant and smoke suppression microspheres, the problem of insufficient flame retardant and smoke suppression performance of existing power cables is solved. At the same time, the flame retardant and smoke suppression microspheres replace halogen-containing compounds to reduce the occurrence of secondary fire disasters;

[0020] 2. The modified microspheres obtained by the reaction and condensation of cyanuric chloride and intermediate 2 with formaldehyde are used as the substrate, and iron oxyhydroxide is grown in situ, and phosphated cyclodextrin is introduced through the inclusion complex between iron oxyhydroxide and cyclodextrin to obtain flame retardant and smoke suppression microspheres:

[0021] Due to the triazine group in the flame retardant and smoke suppression microsphere substrate and the introduced phosphate group, a nitrogen-phosphorus expansion flame retardant system can be formed. And due to the special structure of cyclodextrin, a dense and continuous carbon layer can be formed when a fire occurs, thus achieving a good flame retardant effect.

[0022] At the same time, the three-dimensional structure formed between the in-situ grown iron oxyhydroxide and the modified microspheres greatly expands the surface area of ​​the flame retardant and smoke suppression microspheres, which can have a good smoke absorption capacity and exert a good smoke suppression effect when a fire occurs. DETAILED DESCRIPTION

[0023] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0024] Embodiment 1 A halogen-free flame-retardant power cable comprises, from the inside to the outside, a core, a shielding layer and an outer sheath layer, wherein the outer sheath layer is made of a blended masterbatch;

[0025] A method for preparing a halogen-free flame-retardant power cable comprises the following steps: Step S1: weigh the following raw materials in parts by weight: 60 parts of commercially available AT6101 low-density polyethylene, 10 parts of commercially available 3364 high-density polyethylene, 1 part of di-tert-butyl peroxide crosslinking agent, 0.8 parts of commercially available YBS-S-8600 strontium platinum lubricant, and 6 parts of flame-retardant and smoke-suppressing microspheres, mix the low-density polyethylene, high-density polyethylene, peroxide crosslinking agent, lubricant, and flame-retardant and smoke-suppressing microspheres, add them into a twin-screw extruder, extrude and granulate, and prepare a blended masterbatch;

[0026] Step S2: passing the copper wire into a wire drawing machine, drawing, annealing, and twisting the wire to obtain a wire core, wrapping a mica tape around the outside of the wire core to form a shielding layer, and then extruding the outside of the shielding layer with a blended masterbatch as a raw material to form an outer sheath layer, steam cross-linking, cooling in a water tank, and air-drying in a drying machine to obtain a halogen-free flame-retardant power cable;

[0027] The flame retardant and smoke suppression microspheres are prepared by the following steps:

[0028] Step A1: cyanuric chloride, p-aminobenzenesulfonic acid, sodium carbonate and deionized water are mixed, and sodium bicarbonate solution is added under stirring at a rate of 100 rpm and a temperature of 5°C, and the pH is adjusted to 3, and the reaction is carried out for 1 hour to obtain intermediate 1; intermediate 1, acetone and deionized water are mixed, and ammonia water and sodium hydroxide solution are added under stirring at a rate of 100 rpm and a temperature of 60°C, and the reaction is carried out for 3 hours to obtain intermediate 2;

[0029] The mass concentration of sodium bicarbonate solution is 7.5%, the amount ratio of cyanuric chloride, p-aminobenzenesulfonic acid, sodium carbonate and deionized water is 0.2 mol: 0.2 mol: 10 g: 150 mL, the molar concentration of ammonia water is 10 mol / L, the molar concentration of sodium hydroxide solution is 1 mol / L, and the amount ratio of intermediate 1, acetone, deionized water, ammonia water and sodium hydroxide solution is 0.2 mol: 150 mL: 60 mL: 40 mL: 30 mL;

[0030] Step A2: formaldehyde and deionized water are mixed, and melamine and intermediate 2 are added under stirring at a rate of 120 rpm and a temperature of 80°C, and the mixture is reacted for 20 minutes, and then a formic acid solution is added, and the mixture is reacted for 1 hour, centrifuged, and dried to obtain modified microspheres. The modified microspheres, urea, commercially available K30 polyvinyl pyrrolidone, and deionized water are mixed, and ferric chloride is added under stirring at a rate of 120 rpm and a temperature of 90°C, and the mixture is reacted for 6 hours, centrifuged, and dried to obtain composite microspheres.

[0031] The molar concentration of formic acid solution is 1 mol / L, the dosage ratio of formaldehyde, deionized water, melamine, intermediate 2 and formic acid solution is 20 mL: 300 mL: 0.02 mol: 0.01 mol: 1 mL, and the dosage ratio of modified microspheres, urea, polyvinyl pyrrolidone, deionized water and ferric chloride is 2.5 g: 0.8 g: 15 g: 80 mL: 1.2 g;

[0032] Step A3: β-cyclodextrin, triphenylphosphine, p-hydroxyanisole and acetone are stirred at a stirring rate of 200 rpm and a temperature of 50°C, and pyrophosphoric acid is added to react for 24 hours to obtain phosphated cyclodextrin; composite microspheres, phosphated cyclodextrin, potassium carbonate and tetrahydrofuran are mixed, and stirred at a stirring rate of 80 rpm and a temperature of 85°C for 24 hours to obtain flame retardant and smoke suppression microspheres;

[0033] The dosage ratio of β-cyclodextrin, pyrophosphate, triphenylphosphine and p-hydroxyanisole is 11.2g:0.08mol:0.5g:0.3g; the dosage ratio of composite microspheres, phosphated cyclodextrin, potassium carbonate and tetrahydrofuran is 0.1g:0.2g:0.15g:50-60mL.

[0034] Example 2 A halogen-free flame-retardant power cable comprises, from the inside to the outside, a core, a shielding layer and an outer sheath layer, wherein the outer sheath layer is made of a blended masterbatch;

[0035] A method for preparing a halogen-free flame-retardant power cable comprises the following steps: Step S1: weigh the following raw materials in parts by weight: 70 parts of commercially available AT6101 low-density polyethylene, 15 parts of commercially available 3364 high-density polyethylene, 1 part of di-tert-butyl peroxide crosslinking agent, 1 part of commercially available YBS-S-8600 strontium platinum lubricant, and 6 parts of flame-retardant and smoke-suppressing microspheres, mix the low-density polyethylene, high-density polyethylene, peroxide crosslinking agent, lubricant, and flame-retardant and smoke-suppressing microspheres, add them into a twin-screw extruder, extrude and granulate, and prepare a blended masterbatch;

[0036] Step S2: passing the copper wire into a wire drawing machine, drawing, annealing, and twisting the wire to obtain a wire core, wrapping a mica tape around the outside of the wire core to form a shielding layer, and then extruding the outside of the shielding layer with a blended masterbatch as a raw material to form an outer sheath layer, steam cross-linking, cooling in a water tank, and air-drying in a drying machine to obtain a halogen-free flame-retardant power cable;

[0037] The flame retardant and smoke suppression microspheres are prepared by the following steps:

[0038] Step A1: cyanuric chloride, p-aminobenzenesulfonic acid, sodium carbonate and deionized water are mixed, and sodium bicarbonate solution is added under stirring at a rate of 120 rpm and a temperature of 5°C, and the pH is adjusted to 3, and the reaction is carried out for 1 hour to obtain intermediate 1; intermediate 1, acetone and deionized water are mixed, and ammonia water and sodium hydroxide solution are added under stirring at a rate of 120 rpm and a temperature of 60°C, and the reaction is carried out for 3 hours to obtain intermediate 2;

[0039] The mass concentration of sodium bicarbonate solution is 7.5%, the amount ratio of cyanuric chloride, p-aminobenzenesulfonic acid, sodium carbonate and deionized water is 0.2 mol: 0.22 mol: 10 g: 160 mL, the molar concentration of ammonia water is 10 mol / L, the molar concentration of sodium hydroxide solution is 1 mol / L, and the amount ratio of intermediate 1, acetone, deionized water, ammonia water and sodium hydroxide solution is 0.2 mol: 150 mL: 70 mL: 45 mL: 30 mL;

[0040] Step A2: formaldehyde and deionized water are mixed, and melamine and intermediate 2 are added under stirring at a rate of 120 rpm and a temperature of 80°C, and the mixture is reacted for 30 minutes, and then a formic acid solution is added, and the mixture is reacted for 1 hour, centrifuged, and dried to obtain modified microspheres. The modified microspheres, urea, commercially available K30 polyvinyl pyrrolidone, and deionized water are mixed, and ferric chloride is added under stirring at a rate of 150 rpm and a temperature of 90°C, and the mixture is reacted for 6 hours, centrifuged, and dried to obtain composite microspheres.

[0041] The molar concentration of formic acid solution is 1 mol / L, the dosage ratio of formaldehyde, deionized water, melamine, intermediate 2 and formic acid solution is 22 mL: 300 mL: 0.02 mol: 0.012 mol: 1.5 mL, and the dosage ratio of modified microspheres, urea, polyvinyl pyrrolidone, deionized water and ferric chloride is 3 g: 0.8-1.2 g: 15 g: 80 mL: 1.2 g;

[0042] Step A3: β-cyclodextrin, triphenylphosphine, p-hydroxyanisole and acetone are stirred at a stirring rate of 300 rpm and a temperature of 50°C, and pyrophosphoric acid is added to react for 24 hours to obtain phosphated cyclodextrin; composite microspheres, phosphated cyclodextrin, potassium carbonate and tetrahydrofuran are mixed, and stirred at a stirring rate of 80 rpm and a temperature of 85°C for 24 hours to obtain flame retardant and smoke suppression microspheres;

[0043] The dosage ratio of β-cyclodextrin, pyrophosphate, triphenylphosphine and p-hydroxyanisole is 11.2g:0.1mol:0.5g:0.4g; the dosage ratio of composite microspheres, phosphated cyclodextrin, potassium carbonate and tetrahydrofuran is 0.1g:0.2g:0.18g:60mL.

[0044] Embodiment 3 A halogen-free flame-retardant power cable comprises, from the inside to the outside, a core, a shielding layer and an outer sheath layer, wherein the outer sheath layer is made of a blended masterbatch;

[0045] A method for preparing a halogen-free flame-retardant power cable comprises the following steps: Step S1: weighing the following raw materials in parts by weight: 70 parts of commercially available AT6101 low-density polyethylene, 15 parts of commercially available 3364 high-density polyethylene, 3 parts of di-tert-butyl peroxide crosslinking agent, 1 part of commercially available YBS-S-8600 strontium platinum lubricant, and 8 parts of flame-retardant and smoke-suppressing microspheres, mixing the low-density polyethylene, high-density polyethylene, peroxide crosslinking agent, lubricant, and flame-retardant and smoke-suppressing microspheres, adding the mixture to a twin-screw extruder, and extruding and granulating to obtain a blended masterbatch;

[0046] Step S2: passing the copper wire into a wire drawing machine, drawing, annealing, and twisting the wire to obtain a wire core, wrapping a mica tape around the outside of the wire core to form a shielding layer, and then extruding the outside of the shielding layer with a blended masterbatch as a raw material to form an outer sheath layer, steam cross-linking, cooling in a water tank, and air-drying in a drying machine to obtain a halogen-free flame-retardant power cable;

[0047] The flame retardant and smoke suppression microspheres are prepared by the following steps:

[0048] Step A1: cyanuric chloride, p-aminobenzenesulfonic acid, sodium carbonate and deionized water were mixed, and sodium bicarbonate solution was added under stirring at a rate of 120 rpm and a temperature of 5°C, and the pH was adjusted to 3, and the reaction was carried out for 1.5 hours to obtain intermediate 1; intermediate 1, acetone and deionized water were mixed, and ammonia water and sodium hydroxide solution were added under stirring at a rate of 120 rpm and a temperature of 60°C, and the reaction was carried out for 4 hours to obtain intermediate 2;

[0049] The mass concentration of sodium bicarbonate solution is 7.5%, the amount ratio of cyanuric chloride, p-aminobenzenesulfonic acid, sodium carbonate and deionized water is 0.2 mol: 0.22 mol: 11 g: 160 mL, the molar concentration of ammonia water is 10 mol / L, the molar concentration of sodium hydroxide solution is 1 mol / L, and the amount ratio of intermediate 1, acetone, deionized water, ammonia water and sodium hydroxide solution is 0.2 mol: 160 mL: 70 mL: 45 mL: 40 mL;

[0050] Step A2: formaldehyde and deionized water are mixed, and melamine and intermediate 2 are added under stirring at a rate of 150 rpm and a temperature of 80°C, and the mixture is reacted for 30 minutes, and then a formic acid solution is added, and the mixture is reacted for 1 hour, centrifuged, and dried to obtain modified microspheres. The modified microspheres, urea, commercially available K30 polyvinyl pyrrolidone, and deionized water are mixed, and ferric chloride is added under stirring at a rate of 150 rpm and a temperature of 90°C, and the mixture is reacted for 8 hours, centrifuged, and dried to obtain composite microspheres.

[0051] The molar concentration of formic acid solution is 1 mol / L, the dosage ratio of formaldehyde, deionized water, melamine, intermediate 2 and formic acid solution is 22 mL: 300 mL: 0.025 mol: 0.012 mol: 1.5 mL, and the dosage ratio of modified microspheres, urea, polyvinyl pyrrolidone, deionized water and ferric chloride is 3 g: 1.2 g: 16 g: 100 mL: 1.4 g;

[0052] Step A3: β-cyclodextrin, triphenylphosphine, p-hydroxyanisole and acetone are stirred at a stirring rate of 300 rpm and a temperature of 50°C, and pyrophosphoric acid is added to react for 24 hours to obtain phosphated cyclodextrin; composite microspheres, phosphated cyclodextrin, potassium carbonate and tetrahydrofuran are mixed, and stirred at a stirring rate of 100 rpm and a temperature of 85°C for 24 hours to obtain flame retardant and smoke suppression microspheres;

[0053] The dosage ratio of β-cyclodextrin, pyrophosphate, triphenylphosphine and p-hydroxyanisole is 11.9 g: 0.1 mol: 0.6 g: 0.4 g; the dosage ratio of composite microspheres, phosphated cyclodextrin, potassium carbonate and tetrahydrofuran is 0.12 g: 0.3 g: 0.18 g: 60 mL.

[0054] Comparative Example 1 Compared with Example 3, this comparative example is different in that the phosphated cyclodextrin in the preparation process of the flame retardant and smoke suppression microspheres in Example 3 is replaced by β-cyclodextrin, and the other steps are the same.

[0055] Comparative Example 2 Compared with Example 3, this comparative example replaces the flame retardant and smoke suppression microspheres in the preparation process of the blended masterbatch in Example 3 with commercially available FR-MPP nitrogen-phosphorus flame retardant, and the other steps are the same.

[0056] Take the halogen-free flame-retardant power cables prepared in Example 1, Example 2, Example 3, Comparative Example 1 and Comparative Example 2, peel off the outer sheath layer to make samples, refer to GB / T 2406.2-2009, make them into 80mm×10mm samples, use a limiting oxygen index instrument to test the samples, and test their limiting oxygen index. Refer to GB / T 2408-2021, make them into 125mm×13mm samples, use a horizontal vertical combustion tester to perform a vertical combustion test on them, and refer to ISO 5660-1, use a cone calorimeter at an irradiation intensity of 35kW / m2 Under these conditions, the combustion behavior was recorded and tested, and the test results are as follows:

[0057] Test items Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Limiting oxygen index (%) 33.5 33.9 34.2 31.6 32.8 Vertical burning level V-0 V-0 V-0 V-1 V-0 <![CDATA[Total smoke release amount (m 2 ·m -2 )]]> 3.19 3.22 3.27 4.87 8.98

[0058] It can be seen from the test results in the table shown that when Example 1, Example 2 and Example 3 are compared with Comparative Example 1 and Comparative Example 2, Comparative Example 1 replaces the phosphated cyclodextrin in the preparation process of the flame retardant and smoke suppression microspheres of Example 3 with β-cyclodextrin. Due to the lack of phosphate groups, its flame retardant and smoke suppression performance is greatly reduced. Comparative Example 2 replaces the flame retardant and smoke suppression microspheres in the preparation process of the blended masterbatch of Example 3 with the commercially available FR-MPP nitrogen-phosphorus flame retardant. Due to the absence of a three-dimensional structure, its smoke suppression performance is greatly reduced.

[0059] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0060] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

Claims

1. A method for preparing a halogen-free flame-retardant power cable, characterized in that: It is prepared by the following steps: Step S1: Weigh the following raw materials in parts by weight: 60-70 parts of low-density polyethylene, 10-15 parts of high-density polyethylene, 1-3 parts of peroxide crosslinking agent, 0.8-1 parts of lubricant and 6-8 parts of flame-retardant and smoke-suppressing microspheres, mix the low-density polyethylene, high-density polyethylene, peroxide crosslinking agent, lubricant and flame-retardant and smoke-suppressing microspheres and add them to a twin-screw extruder, extrude and granulate, and prepare a blended masterbatch; Step S2: passing the copper wire into a wire drawing machine, drawing, annealing, and twisting the wire to obtain a wire core, wrapping a mica tape around the outside of the copper-clad aluminum wire core to form a shielding layer, and then extruding the outside of the shielding layer with a blended masterbatch as a raw material to form an outer sheath layer, steam cross-linking, cooling in a water tank, and air-drying in a drying machine to obtain a halogen-free flame-retardant power cable; The flame retardant and smoke suppression microspheres are prepared by the following steps: Step A1: cyanuric chloride, p-aminobenzenesulfonic acid, sodium carbonate and deionized water are mixed, and sodium bicarbonate solution is added under stirring at a rate of 100-120 rpm and a temperature of 5°C, and the pH is adjusted to 3, and the reaction is carried out for 1-1.5 hours to obtain intermediate 1; intermediate 1, acetone and deionized water are mixed, and ammonia water and sodium hydroxide solution are added under stirring at a rate of 100-120 rpm and a temperature of 60°C, and the reaction is carried out for 3-4 hours to obtain intermediate 2; Step A2: formaldehyde and deionized water are mixed, and melamine and intermediate 2 are added under stirring at a rate of 120-150 rpm and a temperature of 80°C, and the mixture is reacted for 20-30 minutes, and then a formic acid solution is added, and the mixture is reacted for 1 hour, centrifuged, and dried to obtain modified microspheres; the modified microspheres, urea, polyvinyl pyrrolidone and deionized water are mixed, and ferric chloride is added under stirring at a rate of 120-150 rpm and a temperature of 90°C, and the mixture is reacted for 6-8 hours, centrifuged, and dried to obtain composite microspheres; Step A3: Stir β-cyclodextrin, triphenylphosphine, p-hydroxyanisole and acetone at a stirring rate of 200-300 rpm and a temperature of 50°C, add pyrophosphoric acid, and react for 24 hours to obtain phosphated cyclodextrin; mix the composite microspheres, phosphated cyclodextrin, potassium carbonate and tetrahydrofuran, stir and react for 24 hours at a stirring rate of 80-100 rpm and a temperature of 85°C to obtain flame retardant and smoke suppression microspheres.

2. The method for preparing a halogen-free flame-retardant power cable according to claim 1, characterized in that: In step A1: the mass concentration of sodium bicarbonate solution is 7.5%, the amount ratio of cyanuric chloride, p-aminobenzenesulfonic acid, sodium carbonate and deionized water is 0.2 mol: 0.2-0.22 mol: 10-11 g: 150-160 mL, the molar concentration of ammonia water is 10 mol / L, the molar concentration of sodium hydroxide solution is 1 mol / L, and the amount ratio of intermediate 1, acetone, deionized water, ammonia water and sodium hydroxide solution is 0.2 mol: 150-160 mL: 60-70 mL: 40-45 mL: 30-40 mL.

3. The method for preparing a halogen-free flame-retardant power cable according to claim 1, characterized in that: In step A2: the molar concentration of formic acid solution is 1 mol / L, the dosage ratio of formaldehyde, deionized water, melamine, intermediate 2 and formic acid solution is 20-22 mL: 300 mL: 0.02-0.025 mol: 0.01-0.012 mol: 1-1.5 mL, and the dosage ratio of modified microspheres, urea, polyvinyl pyrrolidone, deionized water and ferric chloride is 2.5-3 g: 0.8-1.2 g: 15-16 g: 80-100 mL: 1.2-1.4 g.

4. The method for preparing a halogen-free flame-retardant power cable according to claim 1, characterized in that: In step A3: the dosage ratio of β-cyclodextrin, pyrophosphoric acid, triphenylphosphine and p-hydroxyanisole is 11.2-11.9 g: 0.08-0.1 mol: 0.5-0.6 g: 0.3-0.4 g; the dosage ratio of composite microspheres, phosphated cyclodextrin, potassium carbonate and tetrahydrofuran is 0.1-0.12 g: 0.2-0.3 g: 0.15-0.18 g: 50-60 mL.

5. A halogen-free flame-retardant power cable, characterized in that: From the inside to the outside, there are a wire core, a shielding layer and an outer sheath layer, wherein the outer sheath layer is made of a blended masterbatch and is prepared according to any one of the preparation methods described in claims 1-4.

Citation Information

Patent Citations

  • Preparation and application of novel CH2-N=C-Ar group-modified cyclodextrin derivatives

    CN102174125A

  • PS flame-retardant master batch and preparation method thereof

    CN118652450A